The Effect of Work Motivation of Madrasah Principals on Teacher Performance in Madrasah Aliyah Negeri 3 Batanghari Provinsi - Ansori Ansori; Luqmanul Hakim Hawasyi; Usman Handoyo (P3M IAI Nusantara Batang Hari, 2021)
In principle, teachers have a high enough potential to be creative in order to improve their performance. these influencing factors include factors that arise from within the teacher's person, such as the teacher's spersonality, or factors that arise from outside the teacher's person, including motivation. Therefore, every leader in an educational institution needs to have certain strategies to improve performance. Based on the results of observations made by the author on teachers at Madrasah Aliyah Negeri 3 Batanghari, there are various kinds that affect teacher performance, which the author considers to be a problem and is very worthy of further research on.